Tri-component copolymer rods as an implantable reservoir drug delivery system for constant and controllable drug release rate - Tararat Chanlen (2018)
© Springer Science+Business Media Dordrecht 2012. Copolymers of (D,L-lactide-random-ε-caprolactone)-block-poly(ethylene glycol)-block-(D,L-lactide-random-ε-caprolactone) (PLECs) were synthesized with varied D,L-lactide (LA) content and different molecular weights (20 and 50 kDa). Polymer ratios, particularly the content of LA, had significant effect on the release of trypan blue. A lower trypan blue release rate was observed from monolithic rods composed of PLECs with higher CL/LA ratio. High LA content in polymer rod led to increase of the hydrophilicity of the polymer rod and the decrease of CL content resulted in the increase of the hydrophilicity of PLECs and hydrolysis rate. Spin-coating technique was employed to coat PCL-b-PEG-b-PCL membrane on PLEC rod with controlled thickness. Results showed that membrane encased rods can produce different release pattern including delayed release, zero-ordered release and burst release depending on the types of inner rod and membrane. Results for this study indicated that PLEC rods could provide the zero-order release profile of highly water-soluble molecules. Moreover, the longer lag phase was observed at higher thickness. These results suggest that these polymer rods were potential drug delivery systems that can provide controlled drug release profiles.